The Tyranny of Transparency: Auto-immunity in The Teaching Machine - Hoofd, Ingrid Maria (Teorie vědy / Theory of Science, 2016)
The Tyranny of Transparency: Auto-immunity in The Teaching Machine Abstract: This article proposes that the prime ideals of the university - those of truth, knowledge, justice, and emancipation - are also those that currently produce unjust practices "outside" (through aiding social stratification) and "within" (through internal hierarchies and exclusions). Using the work of Jacques Derrida and Paul Virilio, the article argues that the central problem of the university today consists not so much of a neo-liberalisation, but of the speeding-up of these ideals through their enmeshment with techniques of calculation, vision, and prediction. The current university therefore suffers from what it with Derrida identifies as an "auto-immune disease," in which the acceleration of its foundational aspirations have led to a near-total subjugation of all and everything to an oppressive quest for transparency. However, the article proposes via Virilio that this totalising transparency paradoxically also produces more blindness, accidents, and unknowability. It hopes to illustrate this with some examples in the teaching scene as well by working through some of its own conceptual tensions. The other logic of the university today, the article finally proposes, consists of a "dark" or stealth functionality, opening up the promise of a radically different future and unanticipated resistance despite itself. Keywords: transparency; acceleration; neoliberalism; humanism; auto-immunity; teaching; university; vision Tyranie transparentnosti: auto-imunita ve výukovém stroji Abstrakt: Tato studie tvrdí, že hlavní ideály univerzity - pravda, poznání, spravedlnost a emancipace - zároveň produkují nespravedlivé praktiky "vně" (skrze prohlubování sociální stratifikace) a "uvnitř" (skrze interní hierarchie a exkluzi) univerzity. S využitím poznatků Jacquesa Derridy a Paula Virilia se článek zabývá důvody, proč klíčovým problémem současné univerzity není až tak neoliberalizace jako spíše zrychlování těchto ideálů skrze jejich popletenost s technikami kalkulace, vize a predikce. Současná univerzita tak trpí tím, co Derrida identifikuje jako "auto-imunitní nemoc", kdy zrychlování základních aspirací univerzity vede k jejímu téměř totálnímu podrobení všech a všeho represivní snaze o transparentnost. Na pozdí práce Virilia však studie tvrdí, že tato totalizující transparentnost paradoxně produkuje více slepoty, nehod a nepoznatelnosti. Toto tvrzení se argumentace pokouší doložit jak na příkladech z pedagogického prostředí, ale i tak, že rozpracovává některé své vlastní koncepční tenze. Závěrem článek tvrdí, že "temná" nebo též tajná funkčnost přestavuje druhou logiku dnešní univerzity, která navzdory sebe sama, otevírá příslib radikálně jiné budoucnosti a nepředvídatelného odporu. Klíčová slova: transparentnost; zrychlení; neoliberalisms; humanismus; auto-imunita; výuka; univerzita; vize